2008
DOI: 10.2478/v10045-008-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Strains of Entomopathogenic Fungi On Some Main Groups of Soil Microorganisms

Abstract: The influence of entomopathogenic fungal strains -one Metarhizium anisopliae (Metsch.) Sorok. and seven Beauveria bassiana (Bals.-Criv.) Vuill. on some main groups of soil microorganisms was studied after introduction of their conidia into the soil. The soil samples were analyzed for densities of bacteria, actinomycetes and fungi by decimal dilutions of soil suspensions grown on selective media.The presence of conidia of fungal strains in the soil after a month from introduction was proved by bait method. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, of all the entomopathogens, only fungi do not require ingestion or the openings like nematodes to gain entry into their host, but instead use enzymes to penetrate through the cuticle [11]. Among the identified species of fungi, the most utilized are in the genera Beauveria, Cordyceps, Isaria, Lecanicillium, Metarhizium, and Nomuraea, among others, of which several bio-insecticides are attributed [12][13][14]. Due to their ubiquitous nature and ability to survive in different kinds of environments, these entomopathogenic fungi have been tried against insects in several parts of the world and have emerged victorious in many aspects [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, of all the entomopathogens, only fungi do not require ingestion or the openings like nematodes to gain entry into their host, but instead use enzymes to penetrate through the cuticle [11]. Among the identified species of fungi, the most utilized are in the genera Beauveria, Cordyceps, Isaria, Lecanicillium, Metarhizium, and Nomuraea, among others, of which several bio-insecticides are attributed [12][13][14]. Due to their ubiquitous nature and ability to survive in different kinds of environments, these entomopathogenic fungi have been tried against insects in several parts of the world and have emerged victorious in many aspects [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Draganova, Donkova, and Georgieva (2008) showed that lineage 412 of B. bassiana stimulated the growth of soil fungi 30-fold above the control value. Because these microorganisms are heterotrophic, there may be a synergistic interaction between these populations (Draganova et al, 2008).…”
Section: Thiophanate-methylmentioning
confidence: 92%
“…Results obtained by Draganova, Donkova, and Georgieva (2008) showed that lineage 412 of B. bassiana stimulated the growth of soil fungi 30-fold above the control value. Because these microorganisms are heterotrophic, there may be a synergistic interaction between these populations (Draganova et al, 2008). This interaction is important for the degradation of organic soil composts because degradation takes place in stages and includes the action of many physiologically different microorganisms (Stamford, Rodrigues, Heck, & Andrade, 2005).…”
Section: Thiophanate-methylmentioning
confidence: 92%
“…Vuill., L. longisporum and Isaria fumosorosea Wize, have been successfully utilized as biological control agents against numerous pests including aphids (de Faria and Wraight 2007;Powell and Pell 2007;Draganova et al 2008). The main biological attributes for a mycoinsecticide are the virulence toward the target insect and that it is not harmful to other beneficial organisms such as parasitoids and predators (Riddick et al 2009).…”
Section: Introductionmentioning
confidence: 99%